Polygenic liability, stressful life events and risk for secondary-treated depression in early life: a nationwide register-based case-cohort study. Issue 1 (5th May 2021) - Musliner, Katherine L.; Andersen, Klaus K.; Agerbo, Esben; Albiñana, Clara; Vilhjalmsson, Bjarni J.; Rajagopal, Veera M.; Bybjerg-Grauholm, Jonas; Bækved-Hansen, Marie; Pedersen, Carsten B.; Pedersen, Marianne G.; Munk-Olsen, Trine; Benros, Michael E.; et al.
Abstract: Background: In this study, we examined the relationship between polygenic liability for depression and number of stressful life events (SLEs) as risk factors for early-onset depression treated in inpatient, outpatient or emergency room settings at psychiatric hospitals in Denmark. Methods: Data were drawn from the iPSYCH2012 case-cohort sample, a population-based sample of individuals born in Denmark between 1981 and 2005. The sample included 18 532 individuals who were diagnosed with depression by a psychiatrist by age 31 years, and a comparison group of 20 184 individuals. Information on SLEs was obtained from nationwide registers and operationalized as a time-varying count variable. Hazard ratios and cumulative incidence rates were estimated using Cox regressions. Results: Risk for depression increased by 35% with each standard deviation increase in polygenic liability ( p < 0.0001), and 36% ( p < 0.0001) with each additional SLE. There was a small interaction between polygenic liability and SLEs ( β = −0.04, p = 0.0009). The probability of being diagnosed with depression in a hospital-based setting between ages 15 and 31 years ranged from 1.5% among males in the lowest quartile of polygenic liability with 0 events by age 15, to 18.8% among females in the highest quartile of polygenic liability with 4+ events by age 15. Conclusions: These findings suggest that although there is minimal interaction between polygenic liability and SLEs as risk factors for hospital-treated depression, combining information on these two important risk factors could potentially be useful for identifying high-risk individuals.